Excellent Radiological Response with Modern Contemporary Proton Beam Therapy in Favorable Molecular Low-Intermediate Grade Oligodendroglioma: A Report of Two Cases - Tonse, Raees; Noufal, MP; Shamurailatpam, Dayananda; Jalali, Rakesh (Indian Journal of Medical and Paediatric Oncology, 2021)
Radiotherapy (RT) has been a long-standing treatment option for low-grade glioma. Improvements in tumor control and reduced radiation-related toxicity can be attributed to advances in neuroimaging as well as RT treatment planning and delivery techniques. The molecular markers such as isocitrate dehydrogenase and lpl9q play a key role in determining which patients will benefit most from combined radiation and systemic therapy. We hereby report two cases of favorable molecular low-intermediate grade oligodendroglioma treated with modern proton pencil-beam therapy under high-precision image guidance showing excellent radiological response that is usually not seen with conventional photon radiation.
Keywords: low-grade glioma; IDH; oligodendroglioma; proton beam therapy; PCV